أثر النظرة الكونية التوحيدية في صياغة علم العمران الخلدوني : دراسة تحليلية لمفهومي الإنسان والمعرفة في "المقدمة" - مشوش، صالح بن طاهر (Kulliyyat Ma'arif al-Wahy wa 'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2009)
This study examines the Impact of Tawhic worldview on Ibn Khaldun's perceptions of Man, knowledge and al 'Umran (Society). While the positivistic point of view in the Khaldunian Studies is dominating a bulk of more than eight hundred and fifty studies, the present research is designed to introduce an Islamic alternative approach permitting to understand Ibn Khaldun's thought within its vital epistemological and social context. The main hypothesis leading the research in this direction is the reliance of Ibn Khaldun's thought on Tawhidic worldview and Revealed Knowledge sources. To demonstrate the relationship between Ibn Khaldun's thought, specifically Science of 'Umran and Tawhidic worldview, the researcher carry out few tasks, namely re-reading of the biography of Ibn Khaldun and available historical data, tracking the impact of those factors without marginalizing or reducing anyone of them, relating the parts of his thought and approach them all together under a comprehensive system of Tawhidic worldview, and analyze his conceptual core and demonstrate the relation of its elements and meaning under Revealed Knowledge order and standards. Few examples of Ibn Khaldun's argumentation are analyzed in the research, especially his “Natural way of demonstration” which he introduced as an alternative of Aristotelian Logic that he deems unsuitable for the study of 'Umarnic phenomenon which is characterized by complexity, interference, flexibity, change and instability. In addition, some major concept used by Ibn Khaldun such al Fitrah or (human nature) has been stressed in analyzing major themes of the research, i.e., 'Umran, precept of Man, and knowledge. Approaching the mentioned issues, the research adopts a critical method of reading the primary and secondary sources. Defending the Islamicity of Ibn Khaldun's thought is very meaningful in this context, however, the primary objective of the research is to demonstrate the relevance of 'Umranic thought and its methods as introduced by Ibn Khaldun for a better and effective contemporary understanding and reform of the Muslim society. The findings of the research can be summarized as follow: All the aspects of Ibn Khaldun's thought including his worldview is Tawhidic per excellence. In fact, his hypothesis, arguments, demonstrations, analyses, key and operational concepts, criticisms, and laws he applied to phenomenon are reflecting a genuine example of an Islamic way of thinking and conducting a scientific investigation. Consequently, the Ibn Khaldun's 'Ilm al 'Umran as demonstrated in the research possess sufficient epistemological tools which allow such science to be more relevant and gain a solid position to study, reform and change the condition of Muslim society for a better state.